Pembangunan Karakter Siswa SD Ditinjau Dari Latar Belakang Kebudayaan di Lereng Gunung Slamet - Oktaviyanti, Itsna; Pratiwi, Kiki Indah (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
This research aimed to know the process of character building of primary school students and reviewed from the cultural background in Lereng Gunung Slamet. Research method used was qualitative with interpretative approach. Data were collected by using interview and documentation. Then data source was students, teachers, parent of SD Negeri 1 Serang and people while determination of informants used purposive sampling. Data analysis technique was begun by reducing data, presenting data and verification. Research result was that cultural background in lereng Gunung Slamet built students’ characters of SD Negeri 1 Serang. These were because characters built by language elements were friendly and communicative, livelihood elements were discipline, hard work, environmental care, and responsible, religious element were tolerance, honest, loving peace and social care, and last was art and traditional elements where art built characters of creative, loving the homeland , friendly/communicative, and spirit of nationality, while tradition built characters of religious, loving homeland, tolerance spirit of nationality, loving piece, social care and environmental care.